InterPro in 2017—beyond protein family and domain annotations. Issue Volume 45:Issue D1(2017) (28th November 2016) - Finn, Robert D.; Attwood, Teresa K.; Babbitt, Patricia C.; Bateman, Alex; Bork, Peer; Bridge, Alan J.; Chang, Hsin-Yu; Dosztányi, Zsuzsanna; El-Gebali, Sara; Fraser, Matthew; Gough, Julian; Haft, David; et al.
Abstract: InterPro (http://www.ebi.ac.uk/interpro/ ) is a freely available database used to classify protein sequences into families and to predict the presence of important domains and sites. InterProScan is the underlying software that allows both protein and nucleic acid sequences to be searched against InterPro's predictive models, which are provided by its member databases. Here, we report recent developments with InterPro and its associated software, including the addition of two new databases (SFLD and CDD), and the functionality to include residue-level annotation and prediction of intrinsic disorder. These developments enrich the annotations provided by InterPro, increase the overall number of residues annotated and allow more specific functional inferences.